The method of historical writing for western travelers in Al-Ahsa of 1328- 1353 AH/ 1910- 1934 AD - Al-Majnouni, Majdah Attiyah Allah Ahmad (Journal of Humanities & Social Sciences, 2020)
This study seeks to provide a vision as travel literature is an art of Arab literature and a source of archaeological resources to write history.to present a varied picture of the approach of western globetrotters writings about the Arabian Peninsula in general, and the Al-Ehsa'a region and its people in particular, the importance of which is due to its distinguished location on the Arabian Gulf coast that links the west with the East.As the writings of Western globetrotters approaches was drawn up by different points of view in order to reach an appropriate approach for the study of trips literature in general, and to shed light on the methodology of these globetrotters in their writings and their impressions about the Al-Ehsa'a region and to be able to extract an integrated history for the region. To achieve these two aims, it is necessary to review the academic studies concerned with the research.In this study, the researcher used the ethnohistorical approach, which is an approach based on following the methods of the descriptive ethnographic approach, by examining the content of the writings of globetrotters as a research sample, and then following the description through the reality of the observations, and on collecting the scientific material from the books of western globetrotters during that period, and Then study and analyze it.To elicit and extract conclusions from their books as globetrotters and researchers, but in death they only came to collect information and present it to their countries, while they left us with a historical legacy that reveals the extent of their interest in studying Muslim societies, and informs us to know what was in the past after examining and checking it. The most important recommendations: to Establish centers for writing foreign studies, examining and auditing them.
Keywords: history; the Kingdom of Saudi Arabia; Al-Ahsa; writings of Western travelers